2022
DOI: 10.1101/2022.05.18.22275206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequential Organ Failure Assessment (SOFA) score for predicting mortality in patients with sepsis in Vietnamese intensive care units: A multicentre, cross-sectional study

Abstract: ObjectivesTo compare the accuracy of the SOFA and APACHE II scores in predicting short-term mortality among ICU patients with sepsis in an LMIC.DesignA multicentre, cross-sectional study.SettingA total of 15 adult ICUs from 14 hospitals, of which 5 are central hospitals, and 9 are provincial, district, or private hospitals, throughout Vietnam.ParticipantsWe included all patients aged ≥18 years who were admitted to ICUs for sepsis and who were still in ICUs from 00:00 hour to 23:59 hour of the study days (i.e.,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…The variation observed may stem from differences in the patients, pathogens, and clinical ability to care for critically ill patients between low- to middle-income and high-income country settings. (3437) Additionally, the study centre almost only admitted critically ill patients with COVID-19 (92.4%, 85/92; S1 Table in S1 File) who encountered difficulties accessing treatment at lower-level hospitals, with a low rate of intubation (16.7%, 16/96; S1 Table in S1 File) and mechanical ventilation (14.0%, 14/100; S1 Table in S1 File) during transportation. Transferring critically ill patients with COVID-19 from a local to a central hospital may result in the worsening of their critical condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation observed may stem from differences in the patients, pathogens, and clinical ability to care for critically ill patients between low- to middle-income and high-income country settings. (3437) Additionally, the study centre almost only admitted critically ill patients with COVID-19 (92.4%, 85/92; S1 Table in S1 File) who encountered difficulties accessing treatment at lower-level hospitals, with a low rate of intubation (16.7%, 16/96; S1 Table in S1 File) and mechanical ventilation (14.0%, 14/100; S1 Table in S1 File) during transportation. Transferring critically ill patients with COVID-19 from a local to a central hospital may result in the worsening of their critical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Several predictive models have been suggested, but none stands out as significantly superior or precisely predicts the deterioration or mortality in critically ill patients with COVID-19. (34, 35, 5256) Although the APACHE IV score is the most up-to-date version, some centres still use older versions, including the APACHE II score. The present study showed that the APACHE II score had poor discrimination in predicting hospital mortality in critically ill COVID-19 patients (S6 Table in S1 File), aligned with the finding of an earlier published Belgian retrospective study, which also reported a poor discriminatory ability in predicting hospital mortality using the APACHE II score (AUROC: 0.633).…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars contend that its efficacy in predicting mortality at 24 hours and across diverse types of infections may be limited. Furthermore, the score's predictive value may exhibit variability when applied in different economic settings, distinguishing between high-income and low- to middle-income countries [ 10 ]. Despite these acknowledged limitations, the SOFA score retains its merit as a valuable instrument for assessing the severity of sepsis-related organ dysfunction, boasting high accuracy in delineating the course of organ dysfunction in septic patients [ 7 ].…”
Section: Reviewmentioning
confidence: 99%